Personality types and therapeutic communication skills of nurses in hospital - Musta'adah, Iftitatul; Asmaningrum, Nurfika; Kurniawati, Yulia; Faradisa, Elok (JOURNAL OF Mental Health Concerns, 2026)
Background: Personality type is an individual characteristic that influences how nurses interact, communicate, and establish relationships with patients in clinical practice. One of the essential forms of professional interaction in nursing practice is therapeutic communication, which plays a crucial role in building mutual trust between nurses and patients and supporting the healing process. Differences in personality type are presumed to affect nurses’ ability to demonstrate empathy, engage in effective interactions, and respond appropriately to patients’ needs. Purpose: To analyze the relationship between personality type and the therapeutic communication skills of inpatient ward nurses in a hospital setting. Method: A quantitative correlational design with a cross-sectional approach. The study population consisted of all nurses working in the inpatient wards at Jember Klinik Plantation Hospital, totaling 82 nurses. Total sampling was used as the sampling technique. The research instruments included the Jung’s Type Indicator (JTI) to measure personality type and the Global Interprofessional Therapeutic Communication Scale (GITCS) to assess therapeutic communication skills. Data were analyzed using univariate and bivariate analyses, with the point-biserial correlation test applied at a significance level of 5%. Results: The majority of nurses had an introverted personality type (76%). The mean score of nurses’ therapeutic communication skills was 113.82 ± 4.77, which was above the minimum value. The correlation test results showed a significant relationship between personality type and nurses’ therapeutic communication skills (p = 0.000), with a correlation coefficient of r = 0.489, indicating a positive relationship of moderate strength. Conclusion: There was a significant relationship between personality type and the therapeutic communication skills of nurses in inpatient wards. Personality characteristics should be considered as one of the factors in developing strategies to improve therapeutic communication skills in order to enhance the quality of nursing care services. Keywords: Hospital; Nurses; Personality Type; Therapeutic Communication.